Penerapan Corporate Social Responsibility (CSR) Perusahaan Pada Masyarakat (Studi Kasus: PT. Perkebunan Nusantara IV (Persero) Medan) - Arnida Wahyuni Lubis (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara Medan, 2019)
To improve the kesejateraan of the community, the Government makes the partnership and community development program (PKBL) one of them performed by the PTPN XIV IV (Persero) Field which is part State-owned enterprises (SOEs). Basic rules implemented PKBL Minister of BUMN No Per-02/MBU/7/2017 Ministerial Regulation on Amendment No. Per 09/MBU/07/2015 which stated intents and purposes the establishment of STATE-OWNED ENTERPRISES not only pursue profits but undertook to actively provide guidance and assistance to entrepreneurs the weak economy, cooperatives, and communities. The goal in this research is to know the PKBL program implemented PTPN XIV IV (Persero) Field in improving the welfare of society and to find out Why going delinquent installment loans given by the partnership for the activities of SMES. The method used is the representation of the data that comes from a phenomenon faced by the company, and in the analysis by using the approach through an existing theory – theory, namely the decision of the Minister of STATE-OWNED ENTERPRISES, and rare – langkanya is doing the collection with regard to the programme of PKBL, conduct interviews directly and spread sheet observations to parts of PKBL and some people are getting help. The occurrence of a delinquent installment loans that are administered by the partnership for SME activities because there is still I'tikad less laudable than assisted SMEs to afford the repayments, there is a factor of the economy, lack of innovation, the existence of competition between businesses, simply make a new business license, and a factor in the death. Move made to resolve it by way of Monitoring, Reconditioning, Rescheduling, Restructuring.